Study on kinematic characteristics of planetary multistage face gears transmission. (February 2020) - Hu, Qingchun; Chen, Xingbin; Xu, Zhongyang; Mai, Qianli; Zhu, Chune
A planetary gear transmission system with multistage face gears combinations as core component can easily realize the variable speed in differential transmission ratios with structural advantages. In order to improve the transmission stability and loading capacity, it is necessary to set up a reasonable kinematic model for multistage face gears pair. This study focuses on the kinematic characteristics of multistage face gears structure with double crown surface by the methods of numerical calculation and experimental verification. The transmission error and efficiency solving models are established by numerical calculation method to analyze the influences of each factor in detail. Then the correctness of the above numerical models are verified with transmission error and efficiency experiment. In addition, the numerical results are compared with the experimental results to further indicate the important influences of the multistage face gears components on the transmission error and efficiency of whole transmission system. The results can provide references for the dynamic and experimental study of multistage face gears in some degree.